DETERMINAN KEPUTUSAN INVESTASI DI BURSA EFEK INDONESIA - Wahyu Surya Erwansyah (2020)
Investment decision is a sacrifice that a person in the present moment with the aim to get profit in the future. Investment decision making is a process to make or make decisions related to several issues or problems, one of which is making a choice between two or more options that will be an alternative investment or a part of transpformation input into output. The purpose of this research is to know the influence of income, financial literacy and interest rates on investment decisions in the Indonesia stock Exchange. Samples were taken on this study as much as 100 investors as respondents, with non probability sampling methods, purposive sampling. For data collection The respondent is done by spreading the questionnaire to the sample that has been determined through JotForm. Data analysis technique used is a method of analysing PLS (Partial Least Square) with Smart software PLS 3.0. The results of this study show that: (1) Revenue has no influence on investment decisions , (2) Financial literacy has an influence on investment decisions, (3) Interest rates have an influence on the investment.